2010
DOI: 10.1177/1753944709353426
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of isoproterenol-induced cardiac fibrosis in transgenic rats harboring an angiotensin-(1-7)-producing fusion protein in the heart

Abstract: These results indicate that Ang-(1-7) has blood pressure-independent, antifibrotic effects, acting directly in the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 34 publications
4
47
1
2
Order By: Relevance
“…The accumulating evidence that stimulation of the ACE2/Ang-(1-7)/Mas axis produces cardioprotection and antihypertensive effects 8,19,35,39 raises the possibility of development of a next generation of RAS-related drugs aimed to increase the activity of this axis. 34,41 The results presented here, using CGEN-856S, in addition to reinforcing the concept that Mas stimulation produces beneficial cardiovascular effects, illustrates the potential of this novel therapeutic strategy for treating cardiovascular diseases. …”
Section: Perspectivessupporting
confidence: 70%
See 1 more Smart Citation
“…The accumulating evidence that stimulation of the ACE2/Ang-(1-7)/Mas axis produces cardioprotection and antihypertensive effects 8,19,35,39 raises the possibility of development of a next generation of RAS-related drugs aimed to increase the activity of this axis. 34,41 The results presented here, using CGEN-856S, in addition to reinforcing the concept that Mas stimulation produces beneficial cardiovascular effects, illustrates the potential of this novel therapeutic strategy for treating cardiovascular diseases. …”
Section: Perspectivessupporting
confidence: 70%
“…On the other hand, no evidence for a proarrhytmogenic effect of CGEN-856S (this study) or Ang-(1-7) was obtained in vivo. 3,34 We have also observed an antihypertensive effect of CGEN-856S in SHRs. This observation is in accordance with ongoing studies in our laboratory using Ang-(1-7) 29 and with previous reports by others, suggesting that Mas stimulation could be a strategy to treat hypertension.…”
Section: Discussionmentioning
confidence: 70%
“…In their study Ferreira et al observed no differences in heart rate and blood pressure between transgenic rats, overexpressing Ang(1-7) and control rats (Ferreira et al, 2010). Similar to our findings, there was a decrease in coronary flow in transgenic rats.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to the present study, Ferreira et al showed an improved cardiac function, indicated by elevated dp/dt anddp/dt and furthermore, an attenuation of the isoproterenolinduced cardiac fibrosis in transgenic rats. Previous studies also indicated an antifibrotic action of Ang(1-7) in vitro and in vivo (Santos et al, 2004;Ferreira et al, 2010;Dong et al, 2012;McCollum et al, 2012;Acuña et al, 2014). In contrast to these findings, the present study revealed no antifibrotic effect of Ang(1-7) in a transgenic rat model.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation